The role of green spaces in increasing social interactions in neighborhoods with periodic markets. (February 2019) - Aram, Farshid; Solgi, Ebrahim; Holden, Gordon
Abstract: In this research, the effects of green spaces on the extent of residents' socialization behavior as well as the actual presence of people in neighborhood open spaces where daily markets are held, were investigated. The statistical population of this research included residents in six neighborhoods in Hamadan City where daily markets are held. More specifically, social participation in three neighborhoods where the venue of daily markets enjoys green space was compared with three corresponding neighborhoods, where the venue of daily markets lacked green space. The results of the research indicated that in neighborhoods where periodic markets are held in venues with green space, the extent of visits to the market and social behavior, specifically, acquaintance of neighbors with each other, sense of belonging, and the level of cooperation, were greater than that of neighborhoods with no green space. Moreover, effective indices that influence the quality of green spaces were also obtained. These indices, in order of significance, are 1. The aesthetic allure of urban furniture; 2. Suitable vegetation; 3. Sufficiency of urban furniture and; 4. Suitable flooring.